Из истории крымоведения тридцатых: проекты и их реализаторы - Непомнящий, А.А. (Питання історії науки і техніки, 2008)
У статті розглядаються складні тенденції розвитку кримознавства у 30-х роках ХХ століття. До наукового обігу введено джерела щодо намагань відомого радянського історика Б. Д. Грекова реалізувати низку програм з вивчення історії Криму. Відновлено історію підготовки «Повного опису Криму» та першої кримознавчої енциклопедії. Вперше в історіографії встановлено склад краєзнавців, які працювали у річищі виконання цих складних завдань. In the article complicated tendencies of development of Crimean studies in 30th years of
20th century are examined. In the scientific circulation sources concerning attempts of famous
soviet historian B. D. Grekov to realized chain of programs along studying Crimean history
were engaged. History of preparation «Description of Crimea» and encyclopedia of Crimean
studies is renewed. For the first time in historiography staff of regional ethnographers which
had been worked in direction of accomplishment of this complicated task is renewed.